FEATURES OF A CONFIGURATION OF THE EDUCATIONAL ENVIRONMENT OF GENERAL EDUCATIONAL INSTITUTIONS IN THE CONDITIONS OF EXPANSION OF SPECTRUM OF MEANS OF INFORMATION AND COMMUNICATION TECHNOLOGIES - Oleksandra M. Sokolyuk (Information technologies and learning tools, 2011)
Development of information and communication technologies has led to change of a paradigm of knowledge and training environment expansion. The class-lesson system of the organization of educational process was formed as a system of consecutive relaying of knowledge. It is based on the principle of unity of time, a place and a person while the modern paradigm of knowledge expansion demands distribution in time and space. Essentially in new conditions the maintenance of roles of subjects of educational activity has changed also. In the article features of influence on the configuration of computer- focused environment of hardware and software tools of information and communication technologies, decomposition of techniques of their use in educational process of general educational institutions are considered.